Intellectual Property Infringements: Risks and Dangers behind the Phenomenon - Csiki, Olivér Tamás (Magyar Rendészet, 2025)
The aim is to demonstrate the importance of protecting and enforcing intellectual property rights (IPRs) from different perspectives, not only within the dimension of the European Union (EU) but also in relation to certain global actors. The research looked at specific product categories, and their threats to determine which products pose a direct or indirect threat or risk to users, consumers, or the environment. It also focused on the connection with other serious crimes. The research systematically collected, analysed and evaluated reports and studies that are part of the relevant international literature. The study is based on comprehensive statistics and reports published by the European Union Intellectual Property Office (EUIPO), the Organisation for Economic Co-operation and Development (OECD), the World Customs Organisation (WCO) and other relevant EU and non-EU organisations. The IPRs are crucial for the economy of the EU. The IP sensitive industry is responsible for 47.1% of the GDP and 29.7% of employment. On average, 13% of citizens in the 27 EU countries have intentionally bought counterfeit products, during the period under review. The analysis reveals numerous harmful consequences of counterfeiting, such as endangering the health and lives of consumers, non-fulfilment of state revenues and the damage caused to economic operators. In addition to an overview of the problems and an assessment of the hazards, the author has also considered the responses and suggestions for solutions from public – law enforcement authorities and the private sector. Given that the proportion of people aged 15 to 24 who deliberately bought counterfeit goods was twice as high as the average of the EU citizens of all ages, in cooperation with the IP enforcement community, particular attention should be paid to awareness-raising and training and education of youngsters. The conclusions drawn from the results of this work, regardless of their source, are the author’s own and do not necessarily reflect the official position or opinion of the Hungarian National Tax and Customs Administration (NTCA) or of the EUIPO. The publication was prepared with the support of the Scientific Council of the NTCA.